Resilience of Islamic financial institutions amid economic disruptions: lessons from the COVID-19 Pandemic - Suleman, Shahida; Mohd Thas Thaker, Hassanudin; Hina, Fatima; Bhatti, M. Ishaq; Cheong, Calvin Wing Hoh (Springer Nature Singapore, 2025)
The COVID-19 pandemic caused signi!cant disruptions to the global economy, affecting financial systems, including Islamic finance institutions in Organization of Islamic Cooperation (OIC) countries. This study examines the resilience of Islamic banks during the pandemic. Before the pandemic, Islamic financial institutions showed strong growth, supported by non-interest financial instruments that ensured stable liquidity and capital adequacy. However, the crisis revealed vulnerabilities, especially in managing heightened liquidity demands and financial uncertainty. Using Economic Crisis Theory, Systems Theory, and Institutional Theory, this research analyzes Islamic finance’s response to the pandemic, highlighting the role of risk-sharing mechanisms and ethical finance principles in shaping adaptive strategies. Findings indicate that Islamic banks with high-quality capital and robust risk management frameworks exhibited greater resilience, maintaining pro!tability and stability. The study also emphasizes the importance of digital transformation, particularly in FinTech, as a key factor in Islamic banking’s adaptation. Countries such as Indonesia have led in integrating financial technologies, which enhanced returns and supported broader economic recovery. Moreover, Islamic financial tools—such as Qard Hasan, Zakat, Sukuk, Takaful, Istisna, Ijarah, Musharakah, Mudarabah, and endowment fund—played a crucial role in alleviating pandemic-related economic pressures and supporting vulnerable communities. The research advocates for enhanced capital requirements, digital innovation, and a focus on Islamic social finance tools to further strengthen the resilience of Islamic !nance. It contributes to the understanding of Islamic finance’s resilience during crises and provides insights into the potential for digital finance and open innovation within Islamic financial frameworks.